Temporal belief revision rationalized by plausibility orderings - Giacomo Bonanno (University of California, Department of Economics, 2007)
Within the class of structures introduced in [G. Bonanno, Axiomatic characterization of the AGM theory of belief revision in a temporal logic, Artificial Intelligence, 171 (2007), 144-160] we consider the subclass satisfying the property that, for every state-instant pair (omega,t), there is an ordering of the set of states that rationalizes the revised beliefs at every (omega,t') where t' is an immediate successor of t. We characterize this class both semantically and syntactically.
Keywords: 330